Summer larval fish assemblages in the Southern Tyrrhenian Sea (Western Mediterranean Sea). (7th April 2014) - Giordano, Daniela; Profeta, Adriana; Busalacchi, Barbara; Minutoli, Roberta; Guglielmo, Letterio; Bergamasco, Alessandro; Granata, Antonia
Abstract The purpose of this paper was to study the community structure, in terms of species composition, abundance and spatial distribution, of fish larvae in a wide coastal area of Sicily facing the Southeastern Tyrrhenian Sea, extending for 2300 km2 from Cape Cefalù to the west, to Cape Rasocolmo in the east. This study analyses how species are assembled in relation to an inshore–offshore gradient and also how environmental conditions, determined by surface circulation patterns occurring in the Central Mediterranean at the local scale, determine the distribution patterns. Samples from 39 stations were collected using a 60‐cm Bongo net during an ichthyoplanktonic survey carried out in June 2006. In all, 62 taxa, representing 32 families, were identified. Cyclothone braueri (59.6%), Engraulis encrasicolus (9.2%) Lampanyctus crocodilus (4.3%) and Lampanyctus pusillus (4.1%) were the most abundant species. The results showed that the highest abundance value (14830.6 fish larvae per 10 m2 sea surface) was observed in the western part of the study area. MDS, SIMPER and CCA analyses revealed well defined groups of stations and assemblages of larvae in accordance with an inshore–offshore gradient. The results of this study could have implications for the management of marine resources because the investigated area has already been identified as a nursery area for many pelagic and coastal fishes and a natural habitat for many species of high commercial interest.